1999
DOI: 10.1002/(sici)1521-3773(19990315)38:6<786::aid-anie786>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Reverse versus Normal Prenyl Transferases in Paraherquamide Biosynthesis Exhibit Distinct Facial Selectivities

Abstract: Both a face-selective and a non-face-selective mode of formation of quaternary centers of isoprene-derived structural moieties of the natural alkaloid paraherquamide A (1) have been discovered by feeding experiments on Penicillium fellutanum with [U- C ]-glucose and [ C ]-acetate. The labeling patterns suggest that the methyl groups (C22, C23) are introduced in a non-face-selective manner by a reverse prenyl transferase. The C unit comprising the dioxepin moiety retains stereochemical integrity indicative of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 5 publications
1
22
0
Order By: Relevance
“…11,12 These unexpected results pointed to a non-face-selective reverse prenyl transferase. In this case, the olefinic π system of DMAPP is presented in such a manner that both faces are susceptible to attack by the 2-position of the indole moiety.…”
Section: Paraherquamidesmentioning
confidence: 94%
See 1 more Smart Citation
“…11,12 These unexpected results pointed to a non-face-selective reverse prenyl transferase. In this case, the olefinic π system of DMAPP is presented in such a manner that both faces are susceptible to attack by the 2-position of the indole moiety.…”
Section: Paraherquamidesmentioning
confidence: 94%
“…Specific incorporation of intact C 2 units, combined with the 13 C coupling patterns observed by 13 CNMR spectroscopy demonstrated that the isoprene units found in these metabolites arise from dimethylallyl pyrophosphate (DMAPP), a product of the mevalonic acid pathway (Scheme 1). 11,12 …”
Section: Introductionmentioning
confidence: 99%
“…11). 98) These workers carried out feeding experiments in Penicillium fellutanum with [U- 13 C 6 ]-glucose and [ 13 C 2 ]-acetate which aid in distinguishing between the classical mevalonate and deoxyxylulose pathways. Specific incorporation of intact C 2 units was observed, in agreement with the mevalonic acid pathway.…”
Section: )mentioning
confidence: 99%
“…Two possible mechanisms for the formation of this novel ring system have been proposed by Williams et al (Chart 30). 98,99) In the biosynthesis of austamide (10), there are also approximately equal levels of specific 13 C enrichment from in- 99) tact C2 units at the isoprene derived geminal methyl groups. Brevianamide A (2), on the other hand, exhibits significant but incomplete loss of stereochemical integrity in the construction of the reverse prenyl unit.…”
Section: )mentioning
confidence: 99%
“…Isolates from this family of natural products include citrinalins A and B ( 1 and 2 , see Figure 1) and cyclopiamines A and B ( 4 and 6 ), which are the focus of this Article. The modifications of the indole core in the prenylated indole alkaloid family, which occur by a reaction with dimethylallyl pyrophosphate (DMAPP) 1 , results in the introduction of a chromene unit as is found in (+) stephacidin A ( 10 ; see blue highlighted portion) or a bicyclo[2.2.2]diazaoctane core that is typical of many congeners including 11 and 12 (see red highlighted portion) 2 .…”
Section: Introductionmentioning
confidence: 99%